NOXA-Induced Alterations in the Bax/Smac Axis Enhance Sensitivity of Ovarian Cancer Cells to Cisplatin - Lin, Chao; Zhao, Xin-yu; Li, Lei; Liu, Huan-yi; Cao, Kang; Wan, Yang; Liu, Xin-yu; Nie, Chun-lai; Liu, Lei; Tong, Ai-ping; Deng, Hong-xin; Li, Jiong; et al. (PLOS ONE, 2012)
Ovarian cancer is the most common cause of death from gynecologic malignancy. Deregulation of p53 and/or p73-associated apoptotic pathways contribute to the platinum-based resistance in ovarian cancer. NOXA, a pro-apoptotic BH3-only protein, is identified as a transcription target of p53 and/or p73. In this study, we found that genetic variants of Bcl-2 proteins exist among cisplatin-sensitive and -resistant ovarian cancer cells, and the responses of NOXA and Bax to cisplatin are regulated mainly by p53. We further evaluated the effect of NOXA on cisplatin. NOXA induced apoptosis and sensitized A2780s and SKOV3 cells to cisplatin in vitro and in vivo. The effects were mediated by elevated Bax expression, enhanced caspase activation, release of Cyt C and Smac into the cytosol. Furthermore, gene silencing of Bax or Smac significantly attenuated NOXA and/or cisplatin-induced apoptosis in chemosensitive A2780s cells, whereas overexpression of Bax or addition of Smac-N7 peptide significantly increased NOXA and/or cisplatin-induced apoptosis in chemoresistant SKOV3 cells. To our knowledge, these data suggest a new mechanism by which NOXA chemosensitized ovarian cancer cells to cisplatin by inducing alterations in the Bax/Smac axis. Taken together, our findings show that NOXA is potentially useful as a chemosensitizer in ovarian cancer therapy.